FORMULASI DAN UJI FISIK SEDIAAN SALEP EKSTRAK DAUN KERSEN (Muntingia calabura L.) DENGAN VARIASI KONSENTRASI BASIS PEG 400 DAN PEG 4000 - Selvy Adita Nurhaningrum; Umi Nafisah; Ester Dwi Antari (Jurnal Farmasindo, 2021)
Cherry leaves (Muntingia calabura L.) is a medicinal plant that is rarely used by the public. Its use is still traditional so it needs to be made in more practical preparations eg ointments. The purpose of this study was to determine the ethanol extract form of cherry leaves in ointment preparations and make ointment preparations containing ethanol extract of cherry leaves. In this study using an experimental analytical method by making ointment preparations using an ointment base. The basic ointment used is a combination of PEG 400 and PEG 4000, so that 3 formulations obtained with a concentration of 5% cherry leaves. From each formula carried out, the ointment test, organoleptic test, homogeneity test, spreadability test, adhesion test, protection power test and pH test. The results showed that the ointment of cherry leaf extract ointment in F1, F2, and F3 was brownish yellow, distinctive with cherry leaves and semi-solid. Homogeneity test F1, F2 and F3 have homogeneous preparations that meet the parameters. The spread power test of F1 is 2.41 cm, F2 is 2.87 cm and F3 is 4.16 cm does not meet the spread test parameters of 5-7 cm. F1 adhesion test 18.77 seconds, F2 10.1 seconds and F3 6.15 seconds meet the adhesion test parameters not less than 4 seconds. Protection test F1> 5 minutes, F2> 5 minutes and F3> 5 minutes, the longer the red stain appears, the better the protection power, the pH test F1 6.48, F2 6.7 and F3 6.75 do not meet the pH test parameters 4.5 - 6.6. The pH test results obtained a significant value of 0.033 (p <0.05), the results of the test of dispersion and adhesion have the same significant value of 0.027 (p <0.05) which means there is a significant influence on variations in the concentration of PEG 400 and PEG 4000 as base on the physical properties of ointments.